2021
DOI: 10.1016/j.bbrep.2021.101111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of signalling pathways activated by Tyro3 that promote cell survival, proliferation and invasiveness in human cancer cells

Abstract: Tyro3 is a member of the TAM subfamily of receptor tyrosine kinases alongside Axl and MerTK, which are activated by homologous ligands Gas6 and protein S. The TAMs activate signalling pathways that mediate diverse functions including cell survival, proliferation, phagocytosis and immune regulation, and defects in TAM-dependent processes are associated with the development of human autoimmune diseases and numerous cancers. In this study, we have focused on the signalling and functional roles of Tyro3, about whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Although TAM family members have no activation mutations promoting cancer development, studies have suggested that the carcinogenic potential of these members is related to abnormal regulation of the TAM receptor signaling pathway 20 . According to previous studies by others, TYRO3 KD did not significantly affect the expression of AXL and MER in several cancer cells 26,28 . Meanwhile, high TYRO3 expression promotes the drug resistance of tumor cells, and targeted therapy for aberrant TYRO3 activation can effectively improve the drug sensitivity of tumor cells 20,29–31 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although TAM family members have no activation mutations promoting cancer development, studies have suggested that the carcinogenic potential of these members is related to abnormal regulation of the TAM receptor signaling pathway 20 . According to previous studies by others, TYRO3 KD did not significantly affect the expression of AXL and MER in several cancer cells 26,28 . Meanwhile, high TYRO3 expression promotes the drug resistance of tumor cells, and targeted therapy for aberrant TYRO3 activation can effectively improve the drug sensitivity of tumor cells 20,29–31 .…”
Section: Discussionmentioning
confidence: 94%
“…20 According to previous studies by others, TYRO3 KD did not significantly affect the expression of AXL and MER in several cancer cells. 26,28 Meanwhile, high TYRO3 expression promotes the drug resistance of tumor cells, and targeted therapy for aberrant TYRO3 activation can effectively improve the drug sensitivity of tumor cells. 20,[29][30][31] To explore the role of TYRO3 in GC cells, we knocked down TYRO3 expression in GC cell lines and analyzed the changes in the proliferation and migration ability of GC cells.…”
Section: Tyro3 Promoting Gastric Tumorigenesis and Worsening Nutritio...mentioning
confidence: 99%
“…Gas6 activates all three TAM receptors, with greatest affinity for Axl followed by Tyro3 then Mer, whereas ProS1 is a ligand for Tyro3 and Mer only [ 11 ]. We have shown that ProS1 is a preferred ligand for Tyro3 over Gas6 in human cancer cells expressing both Tyro3 and Axl receptors [ 30 ], as well as identified Tyro3 signaling pathways that progress the cell cycle and support survival in cancer cells [ 50 ]. However, while there is insight into the structure-function relationships that exist for the Gas6-Axl interaction [ 23 ], no such knowledge exists on the nature of the ProS1-Tyro3 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…While their specific role often varies depending on the cellular context, the TAM receptors are typically associated with prosurvival signaling, invasion, and migration. Axl has been implicated in metastasis, migration, invasion, and drug resistance in a number of different cancers. , Mer activity has also been tied to motility and survival signaling under varying contexts. There are fewer studies on the individual role of Tyro3 compared to Axl and Mer, but despite being understudied, Tyro3 remains an important cancer target as well. …”
Section: Introductionmentioning
confidence: 99%